TRANSLATION OF PROVERBS FROM ENGLISH INTO UZBEK: PROBLEMS OF EQUIVALENCE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The translation of proverbs represents one of the most difficult areas of translation studies because proverbs combine linguistic form with cultural meaning. This article explores the challenges of translating English proverbs into Uzbek with special attention to the problem of equivalence. The research discusses semantic, stylistic, pragmatic, and cultural aspects of equivalence and explains why literal translation often fails to preserve the original meaning. The article also examines the relationship between language and culture through comparative analysis of English and Uzbek proverbs. Different translation strategies such as descriptive translation, cultural substitution, and communicative translation are analyzed with examples. The study demonstrates that successful proverb translation depends not only on linguistic accuracy but also on intercultural understanding and contextual adaptation. The findings of the research may contribute to the development of comparative linguistics, paremiology, and translation methodology.
Keywords: Proverb translation, equivalence, translation studies, cultural adaptation, semantic meaning, communicative translation, English language, Uzbek language, paremiology, intercultural communication.